Dyslexic Students’ Profiles in Vocational Schools: Characteristics and Strategies - Mukhlis, Muhammad; Sohnui, Suhailee; Asnawi, Asnawi; Yuliawan, Tri; Shafina, Vira; Siburian, Desi Arni Natalina Br (Universitas Negeri Makassar, 2025)
Inclusive education aims to provide equal learning access for all students, including those with special needs such as dyslexia. This study explores the characteristics of students at risk of dyslexia in Vocational High Schools (SMK) and the learning strategies that can be implemented to improve their reading skills. Using a descriptive qualitative approach, data was collected from 11 Indonesian language teachers at public vocational schools in Pekanbaru through questionnaires and Focus Group Discussions (FGD). The findings indicate that dyslexic students face difficulties in letter recognition, reading fluency, and text comprehension, which impact their self-confidence and motivation to learn. The learning strategies currently applied in schools have not been fully adapted to the needs of dyslexic students, relying heavily on text-based methods without incorporating multisensory approaches or adaptive technology. Furthermore, the assessment methods still follow conventional formats, making it difficult for dyslexic students to demonstrate their understanding optimally. Therefore, more adaptive learning approaches are needed, such as multisensory methods, explicit phonics instruction, and the integration of assistive technology to enhance the literacy skills of dyslexic students. These findings are expected to serve as a foundation for developing more inclusive educational policies and improving teachers' competencies in supporting students with special needs in vocational school environments.